THE IMPLEMENTATION RELIGIOUS MODERATION IN SERANG MUNICIPIAL: RELIGIOUS HARMONY FORUM PERSPECTIVE - Rizky Aditya; Ima Mayasari (Penamas, 2022)
Religious moderation is still being promoted by the Indonesia government because it is seen as having strategic value for the development of religious understanding in the religious field. This study aims to describe the implementation of the concept of religious moderation which has been carried out by the people of Serang Municipial, Banten Province without realizing it. Forum of Religious Harmony as an institution that represents the community has an important role in implementing the concept of religious moderation. By using a qualitative approach, this study aims to explore the implementation of religious moderation in Serang Municipial in strengthening local culture, building tolerance and practicing religious moderation in Serang Municipial. The results of this research study confirm that the religious moderation of the Serang community, according to the Religious Harmony Forum has been embedded from the past, cultural acculturation that has been built since the monarchy era shows that the prior life of the Serang Municipial community prioritizes things that are balanced and moderate.